The development of ecotourism and ways to sustain it (The million visits to the Holy Karbala as a model) - Mohammed Dabbagh, Adnan (International Journal of Psychosocial Rehabilitation, 2021)
The most important reason for the emergence of ecotourism at the present time is the rapid development witnessed by the global tourism movement and the emergence of mass tourism, which led to a large number of environmental and social negatives in most countries of the world. This resulted in an urgent need for other forms of tourism as alternatives to traditional tourism that affect the environment. This means that ecotourism is an alternative form of tourism that focuses on marginal areas. Secondly, environmental tourism is not a new type of tourism but rather a set of ideas and broad lines all aimed at maintaining the tourist, cultural, archeological, and natural components with all its elements according to a long-term strategic plan.Therefore, there is an urgent need to conduct a field study to find out the reality of environmental tourism in Karbala due to its religious and cultural legacy, which attracts millions of visitors each year. Given its great importance, the researcher is conducting a field study to learn about the reality of these visits and their impact on the environment, with the core focus of the study being the changes that have occurred since 2003. Emphasis is placed on sustainability factors and development, and the researcher seeks to gather data from various tourism sectors inside and outside Iraq for the purpose of analyzing the results and testing hypotheses.The most important conclusions will then be drawn, and recommendations will be made with the aim of developing environmental tourism in Holy Karbala, particularly during times of high visitation